A multi-criteria approach to the integration andf evaluation of investment portfolios - Muñoz, Manuel; Alvarez, Pavel; Miranda, Eva; León Castro, Ernesto (2021)
One of the problems that investors often face is deciding on the stocks to include in an investment portfolio. The objective of the article is the selection of investment portfolios considering the 30 main companies listed on the New York Stock Exchange of the Dow Jones Index. Portfolio selection in this index is carried out by generating a previous ranking of the shares with a novel approach that analyzes the performance of the shares in a Multiple Criteria Hierarchical Process (MCHP). The ordering is generated with the hierarchical version of the ELECTRE III method using different decision criteria based on financial ratios.